Issues of market monopolization in the mining of non-metallic minerals in transition economies - Aleksandr K Kirsanov; Evgenii P Volkov; Natalia A Shkaruba; Natalia V Nikolaeva; Umarjon R Teshaev (Brawijaya University, 2022)
This paper considers the issue of mining non-metallic (rock) products in the context of transition economies. Our studies have shown that interest in non-metallic products is growing every year, as evidenced by the growing volumes of production both around the world and in the group of countries considered in the article. The market analysis for non-metallic minerals has revealed the market development dynamics; however, its high monopolization may lead to some restrictions on free competition in subsoil use. In order to assess such monopolization, we have calculated the Herfindahl-Hirschman index for each non-metallic mineral mined in countries with economies in transition. We have found that the entire product range under consideration is part of a highly concentrated market dominated by the Russian Federation. We have presented some options for designing and introducing various kinds of arrangements to develop the mining potential of non-metallic minerals in order to reduce the dominant component of individual countries or companies and to balance the market. It is proposed to consider a partial transition from the possibility of developing deposits to an underground one — as an alternative option that harms the environmental load on the situation in the mining area. The results of this study will be used to conduct a detailed analysis in each country under review, which will provide the most complete picture of the mining industry in countries with economies in transition.